DNA profiling of unidentified human remains in the South African context: an ethico-legal analysis - Krysztofiak, Bozena (My University, 2016)
Due to the inherent sensitive character of human genetic material, when employing DNA-based methodology in identification of human remains, clear ethical guidelines and well implemented law are necessary. With this in focus, the study determines and validates a set of morally justifiable ethical standards drawn from universal principles and human rights which rest on the value of respect of human dignity. In South Africa, The Criminal Law (Forensic Procedures) Amendment Act was commenced in 2015. While the terms of the Act mainly deal with the establishment and functioning of the National Forensic DNA Database of South Africa for the purposes of criminal justice, it also provides for the identification of missing persons and unidentified human remains. To be fully compliant with ethical standards and human rights, few areas of the Act needing attention and improvement during a further implementation process are highlighted. This study concludes with several recommendations to promote meeting the recognised ethical standards by the local DNA-based programme of identification of human remains.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Medicine in Bioethics and Health Law Johannesburg, December 2016
Keywords: DNA Fingerprinting; DNA Fingerprinting; Body Remains; Criminal Law